Distal Splenorenal Shunt for Portal Vein Thrombosis after Liver Transplantation - Marino, Ignazio R. (1989)
A 17-yr-old female received a liver transplant for type I glycogen storage disease. A year later, when she experienced variceal gastrointestinal hemorrhage, an angiogram revealed thrombosis of the portal vein with hepatopetal collateral channels. A distal splenorenal shunt was performed because of failure of sclerotherapy to control subsequent bleeding episodes and the fact that the liver function was normal. This patient continues to have normal hepatic function with a patent splenorenal shunt 4 yr after the shunting procedure. This case illustrates the feasibility of a distal splenorenal shunt to alleviate portal hypertension in cases of thrombosis of the portal vein following hepatic transplantation if the liver function is normal.